Rekonstruksi Pemikiran Kartini tentang Keagamaan untuk Memperkuat Integrasi Nasional - Lilis Muchoiyyaroh (Diponegoro University, 2019)
Kartini's complex thinking about her nation was the result of observations and experiences that she experienced empirically. But Kartini's ideas about religion were explicitly influenced by the surrounding environment, both European and indigenous people themselves. This study focuses on the reconstruction of Kartini's thinking in the field of religion and the social background of the emergence of this thought. Therefore, this study uses historical methods with a social history approach to identify Kartini's ideas in the religious field. The reconstruction of her ideas as one of the national integration efforts that cannot be separated from the influence of the religiosity and social background of the people around her. Kartini's thinking about religion was critical, open, and pluralistic, which was concerned with the division of the nation due to religious differences.